CIRC and Reading Comprehension Achievement: The Effect and Their Interaction with Self Efficacy - Gysela Debby Utari; Anissa Astrid; Deta Desvitasari (Universitas Muhammadiyah Tangerang, 2026)
This study aimed to examine the effect of Cooperative Integrated Reading and Composition (CIRC) on students’ reading comprehension achievement, viewed from their level of self-efficacy. The research was conducted at SMAN 2 Unggulan Talang Ubi and applied a quantitative approach with a factorial experimental design. The participants were eleventh-grade students. The findings of this study are as follows: 1) There was a significant difference in students’ reading comprehension achievement between those taught using the CIRC method and those taught using a conventional method; 2) There was no significant difference in reading comprehension achievement between students with high and low self-efficacy; and 3) There was no significant interaction between the teaching method and students’ self-efficacy level in influencing reading comprehension achievement.These results indicate that CIRC is an effective teaching strategy to enhance students’ reading comprehension. However, students’ self-efficacy alone may not directly influence achievement without additional support or intervention. The study underscores the importance of applying interactive and student-centered instructional methods to improve learning outcomes.